ANALYSIS CORPORATE GOVERNANCE AND COMPANY CHARACTERISTICS OF PUBLICATION OF SUSTAINABILITY REPORT ON COMPANIES IN INDONESIA STOCK EXCHANGE - Adelia Ramadan; Vargo Christian L. Tobing (Enrichment : Journal of Management, 2022)
The purpose of this studies was to determine the effects of the audit committee, board of directors, and company characteristics simultaneously on the publications of sustainability reports on companies on the Indonesia Stock Exchange. This researches was a quantitative researches. The participants in this study were all mining companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sample size of this research is 8 companies. The results of the studies conclude that the audit committee and company size has a significants effects on the publications of sustainability reports on mining sector companies listed on the Indonesia Stock Exchange. However, the boards have no significants effects on the publication of sustainability reports on mining sector companies listed on the Indonesia Stock Exchange.